What do we know about business and economics research during COVID-19: a bibliometric review. Issue 1 (31st December 2022) - Alshater, Muneer M.; Atayah, Osama F.; Khan, Ashraf
Abstract: The destructive COVID-19 has emerged as the most lethal disease and dented the global economies in every aspect. Consequently, a large amount of research emerged to understand the dynamics of COVID-19. Using meta-literature approach with combination of both bibliometric (quantitative) and content analysis (qualitative) approach, this study aims to present a comprehensive review of COVID-19 business-related research of 477 articles. The results reveal the most the most relevant and influential scientific aspects of the literature such as authors, articles, institutions, journals, and countries. We also identify intellectual structure within six streams: 1) COVID-19 and global economy, 2) Dynamics of COVID-19 in business and management research, 3) COVID-19 and financial markets, 4) COVID-19 and its implication for tourism & hospitality industry, 5) Dynamic of supply chain and COVID-19 and 6) COVID-19 and functionality of government. Lastly, the review of the literature helps us to identify the research gaps and present 62 future research directions.